2018
DOI: 10.1177/1129729818761277
|View full text |Cite
|
Sign up to set email alerts
|

Haemodialysis access thrombosis: Outcomes after surgical thrombectomy versus catheter-directed thrombolytic infusion

Abstract: Thrombolysis for thrombosis of native and prosthetic dialysis accesses appears to yield better assisted primary patency compared to surgical thrombectomy. Our results suggest that thrombolysis may be considered the first-choice method for treating the thrombosed dialysis access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 20 publications
2
17
0
1
Order By: Relevance
“…There are treatment methods of thrombotic occlusion in VA currently in the main stream such as surgical thrombectomy, thrombolysis device, thrombus fragmentation device or thrombus suction device, and so on. These methods show a good result for a long period as in the previous works, 510 but, except for surgical thrombectomy, they require medical treatment during the hyperacute phase after obstruction. Fragmentation will be impossible when time passed after obstruction as the thrombus degenerates and stiffens.…”
Section: Discussionmentioning
confidence: 62%
“…There are treatment methods of thrombotic occlusion in VA currently in the main stream such as surgical thrombectomy, thrombolysis device, thrombus fragmentation device or thrombus suction device, and so on. These methods show a good result for a long period as in the previous works, 510 but, except for surgical thrombectomy, they require medical treatment during the hyperacute phase after obstruction. Fragmentation will be impossible when time passed after obstruction as the thrombus degenerates and stiffens.…”
Section: Discussionmentioning
confidence: 62%
“…Concerning the one-year secondary patency rate, the 82.6% and 56.3% rates of one-year secondary patency in the endovascular and open thrombectomy groups in the present study are in some ways different and in some ways comparable to the results reported by Tordoir, et al (23-62% and 27-65%) and Hongsakul, et al (54.3% and 57%). Recent study from Koraen-Smith, et al 12 show the same results that thrombolysis group had better assist primary patency.…”
Section: Discussionmentioning
confidence: 66%
“…Mostly of patients had total graft thrombosis, only 11 of 25 patients in the endovascular group presented with clinical partial graft thrombosis. Median time from graft thrombosis to treatment was 2 days (range: 1-14) in the endovascular group, and 1 day (range: [1][2][3][4][5][6][7][8][9][10][11][12][13][14] in the open thrombectomy group (p=0.078). A summary of patient and graft data is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…It remains elusive whether the increased epistaxis was associated with higher blood pressure. It was reported that 4% (4/107) of patients who underwent surgical thrombectomy suffered a post-operative infection and required a repeated procedure and antibiotic therapy (20). Endovascular interventions are associated with embolization (21-23), in particular arterial emboli, which occur in >6% of patients receiving percutaneous declotting (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the present study has certain limitations. The size of the thrombi was not measured and the study did not focus on underlying stenosis, while these two parameters may constitute as confounding factors (20). Another limitation of the study was the lack of long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%